Techno-instructional application in a MOOC designed with gamification techniques - Agila Palacios, M. (2016)
This paper describes the experience of integration of gamification activities in a Mooc, starting from the techno-instructional Mooc design, making emphasis on technologies that support the model that is presented; to reach results on the level of interaction and student satisfaction. For this, a survey was conducted and analysis of data recorded in the Moodle 2.6 platform on which gamification plugins were integrated. The results show that gamification strategies applied, allow to increasing the percentage of approval, it usually takes the Moocs, reaching 39% compared to participants who started, and 95% compared to the active participants in the last week.